2009
DOI: 10.1007/s00464-009-0723-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating outcomes of endoscopic full-thickness plication for gastroesophageal reflux disease (GERD) with impedance monitoring

Abstract: Endoscopic full-thickness plication significantly reduced total reflux episodes, acid reflux episodes, and total reflux exposure time. The DeMeester scores and total acid exposure time for the distal esophagus were significantly improved. No significant changes in nonacid reflux episodes and median bolus clearance time were encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
8
0
2
Order By: Relevance
“…The data of this study clearly demonstrate that symptom improvement does not apply to the placebo effect, as documented by the results of MII monitoring. Furthermore, previously reported MII findings by von Renteln et al, 24 who evaluated gastroplication outcomes 6 months after procedure are confirmed here. The study demonstrates a significant reduction of DeMeester scores and of total, acid, proximal, upright, and recumbent reflux episodes, despite unchanged LES parameters.…”
Section: Discussionsupporting
confidence: 89%
“…The data of this study clearly demonstrate that symptom improvement does not apply to the placebo effect, as documented by the results of MII monitoring. Furthermore, previously reported MII findings by von Renteln et al, 24 who evaluated gastroplication outcomes 6 months after procedure are confirmed here. The study demonstrates a significant reduction of DeMeester scores and of total, acid, proximal, upright, and recumbent reflux episodes, despite unchanged LES parameters.…”
Section: Discussionsupporting
confidence: 89%
“…We chose to measure reflux postoperatively with the intent to demonstrate that the TIF procedure produces objectively identifiable changes in the amount of esophageal acid exposure that correlate with symptom improvement. Utilization of a telemetry capsule pH probe was favored over transnasal impedance testing because of patient acceptance, even though it did not provide us with information on nonacid reflux events [47, 48]. In our research protocol we defined pH-metric success by normalization of one or more of the acid reflux characteristics such as acid exposure, number of refluxates, or DeMeester score.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this treatment option has been showed to eliminate the need for maintenance antacid therapy in a large proportion of patients [11]. Along with subjective symptom improvement, endoscopic plication seems to also improve objective evidence of reflux [12].…”
mentioning
confidence: 98%